An efficient DNA extraction method from bone and tooth samples by complete demineralization followed by the use of silica-based columns (Dhaka University Journal of Biological Sciences, 2014)
A highly efficient strategy for recovery of genomic DNA from bone and tooth samples is presented by complete demineralization of the bone pieces or intact tooth with high concentration of EDTA followed by spin column treatment without the need of mechanical grinding or cryogenic method for pulverizing the samples. The DNA yield was between 8 and 12 ng/?l from approximately 1 ?2 g of the starting material. Completed DNA profiles were obtained from of all the bones (52) and tooth (270) samples received from the unidentified victims from a recent building collapse, the Rana Plaza disaster in Dhaka, Bangladesh. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20089 Dhaka Univ. J. Biol. Sci. 23(2): 101-107, 2014